CORPORATE GOVERNANCE: CHALLENGE OF ACCOUNTING PROFESSION - Pastor Carrasco, Carlos Alberto (2011)
The overall objective of our research is to: Identify the extent to which accounting serves as a mechanism for reducing the asymmetry of information and assists in implementing good corporate governance in companies of our country. The theoretical framework of accounting, it lacks a static structure, and is influenced by other disciplines, as reflected in the impact over the past thirty years has received. The importance of corporate governance became dramatically clear in 2002 that occurred due to a series of corporate mergers, fraud, other catastrophes that led to the destruction of billions of dollars of shareholder wealth, loss of thousands of jobs work, criminal investigations of dozens of executives and record bankruptcies. Our research concludes by recommendations, from the accounting point of view, may be implemented in businesses to achieve good corporate governance.